The big picture medical biochemistry - Janson, Lee W. (McGraw-Hill, 2012)
Medical Biochemistry: The Big Picture is a unique biochemistry review that focuses on the medically applicable concepts and techniques that form the underpinnings of the diagnosis, prognosis, and treatment of medical conditions. Those preparing for the USMLE, residents, as well as clinicians who desire a better understanding of the biochemistry behind a particular pathology will find this book to be an essential reference. Featuring succinct, to-the-point text, more than 300 full-color illustrations, and a variety of learning aids, Medical Biochemistry: The Big Picture is designed to make complex concepts understandable in the shortest amount of time possible. This full-color combination text and atlas features: -Progressive chapters that allow you to build upon what you've learned in a logical, effective manner -Chapter Overviews that orient you to the important concepts covered in that chapter -Numerous tables and illustrations that clarify and encapsulate the text -Sidebars covering a particular disease or treatment add clinical relevance to topic discussed -Essay-type review questions at the end of each chapter allow you to assess your comprehension of the major topics -USMLE-style review questions at the end of each section -Three appendices, including examples of biochemically based diseases, a review of basic biochemical techniques, and a review of organic chemistry/biochemistry